2018
DOI: 10.1253/circj.cj-18-0417
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and Prognostic Values of Appearance of L Wave in Heart Failure Patients With Preserved vs. Reduced Ejection Fraction

Abstract: Appearance of L wave is associated with the degree of LV diastolic dysfunction, but there was a difference in LV geometrical correlates of the appearance of L wave between the HFpEF and HFrEF groups. Detection of L wave is suggestive of poor prognosis independent of LVEF in HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…There were 10 bpm difference between the presence and the absence of A wave in the HR of L wave disappearance. These findings are consistent with the previous reports describing that L wave is more likely to be observed in patients with AF and lower HR [3], [4]. In the condition with the presence of A wave, A wave occupied late diastolic phase and shortened the time for L wave existence (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…There were 10 bpm difference between the presence and the absence of A wave in the HR of L wave disappearance. These findings are consistent with the previous reports describing that L wave is more likely to be observed in patients with AF and lower HR [3], [4]. In the condition with the presence of A wave, A wave occupied late diastolic phase and shortened the time for L wave existence (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…L wave is occasionally detected in patients with heart failure and regarded as an indicator of diastolic dysfunction [2], [5]. Some previous researchers have reported that regardless of ejection fraction, L wave is more likely to be observed in heart failure patients with lower HR, higher LV filling pressure and AF, and the presence of L wave is associated with poor prognosis [3], [4], [6]. However, in these reports, L wave was observed not for a certain duration but at a specific point of time, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mid-diastolic events (L events). presence as a marker of advanced diastolic dysfunction and increased risk of adverse cardiac events [15][16][17][18]. L events are affected by heart rate (HR), cardiac rhythm, and loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It was called “L” because it follows the K and J pulmonary vein flow phases (corresponding to the S and D waves of pulmonary venous flow Doppler sampling). Although L waves were first reported in healthy individuals, many studies indicate their presence as a marker of advanced diastolic dysfunction and increased risk of adverse cardiac events [ 15 , 16 , 17 , 18 ]. L events are affected by heart rate (HR), cardiac rhythm, and loading conditions.…”
Section: Introductionmentioning
confidence: 99%